Деякі особливості фольклорної інструментальної традиції Західної України у першій третині ХХ ст. - Дрозда, П. (Студії мистецтвознавчі, 2008)
The author tells about some features of folk performance in Western Ukraine in the beginning of the 20th century as well as perceptions of the instrumental tradition in composer professional creativity.